Pelatihan Manajemen Pertunjukan Virtual Seni Anak Usia Dini Berbasis Budaya Lokal - Intan Prastihastari Wijaya; Dema Yulianto; Linda Dwiyanti; Itot Bian Raharjo; Sita Aulia Rahma (Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2022)
Early childhood art performance management training is given to kindergarten teachers to make it easier for teachers to manage the need to organize virtual art performances for early childhood, and while still paying attention to the psychological aspects of early childhood. The participants of this local culture-based early childhood virtual art performance management training were representatives of the 12 people of Pokja 02 Kediri City Kindergarten teachers, and the implementation took place at Santo Yoseph II Kindergarten, Kediri City. The methods used in this training are lectures, question and answer discussions and demonstrations, and mentoring. The main resource persons for this training were the chairperson and members of the team proposing the application of science and technology for the community, namely 4 people, assisted by 1 student. The results of this local culture-based early childhood virtual art performance management training are very useful for teachers. It is felt that most teachers still lack the knowledge and skills to design virtual art performances for early childhood, and the training organized is very helpful for teachers in designing ideas for virtual art performances for early childhood.